Anti-inflammatory potential of Agaricus in carrageenan-induced model of local inflammation in rats - Elmajdoub, Abdelrazzag A.; Awidat, Shaban Kh.; El-Mahmoudy, Abubakr M. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The concept of effects of Agaricus on inflammatory responses is still controversial. This study, therefore, was designed to assess the potential of the anti-inflammatory effect of Agaricus 100% extract on acute inflammation using the model of carrageenan-induced paw edema in rats. Methods: Four groups among five (six rats each) have been injected with carrageenan (0.1 mL of 3% solution), intra-plantar in the right hind paw; the first group was injected with saline instead in the same manner and kept as control. An hour earlier, rats received different treatments, either saline (inflamed control), or diclofenac (inflamed, standard-treated), or Agaricus extract (5 mL/kg as small dose or 10 mL/kg as a large dose). The volume of the developed paw edema has been measured at an hour interval fashion (1 6 hrs) and at 24 hrs. Results: Agaricus extract showed inhibitory effects on the carrageenan-induced edema in time- and dose-dependent manner, at the late phase (2 hrs) of the inflammatory response (small dose) and at both early ( 2 hrs) and late phases (large dose). The effects were comparable to those of diclofenac being 11.74, 08.46, 08.99, 09.72 and 09.89% at 2-6 hrs (small dose); 14.04, 23.91, 21.92, 17.99, 15.63 and 16.96% at 1-6 hrs (large dose); 16.85, 31.30, 35.38, 35.97, 34.72 and 34.63% (diclofenac). The anti-inflammatory effect of Agaricus could be attributed to its phytochemical content which may inhibit the inducible inflammatory mediators (as prostaglandins and nitric oxide) in the late phase (small dose) and/or inhibiting both early (histamine and oxygen free radicals) and late mediators (large dose). Conclusions: These data may indicate that Agaricus extract has the potential of anti-inflammatory activity that could be applied in acute inflammatory disorders.